How Study Environments Foster Academic Procrastination: Overview and Recommendations - Svartdal, Frode; Dahl, Tove I.; Gamst-Klaussen, Thor; Koppenborg, Markus; Klingsieck, Katrin B. (Frontiers in Psychology, 2020)
Abstract Procrastination is common among students, with prevalence estimates double or even triple those of the working population. This inflated prevalence indicates that the academic environment may appear as "procrastination friendly" to students. In the present paper, we identify social, cultural, organizational, and contextual factors that may foster or facilitate procrastination (such as large freedom in the study situation, long deadlines, and temptations and distractions), document their research basis, and provide recommendations for changes in these factors to reduce and prevent procrastination. We argue that increased attention to such procrastination-friendly factors in academic environments is important and that relatively minor measures to reduce their detrimental effects may have substantial benefits for students, institutions, and society.